DETEKSI PENYAKIT TILV (Tilapia Lake Virus) PADA IKAN NILA (Oreochromis niloticus) DENGAN METODE RT-PCR DI BALAI KIPM MEDAN I - Mulana Saragih; Junaidi (Universitas Mataram, 2021)
Lately in some areas there have been cases of death in the cultivation of tilapia fish en masse which is likely to be an infection of TiLV disease. TILV that attacks tilapia can be quick diagnosed with RT - Polymerase Chain Reaction (RT-PCR) method. This examination method detect the virus through the presence of its RNA. The purpose of this study is to determine the effectiveness of RT-PCR method in detecting disease in tilapia (Oreochromis niloticus) at the Fish Quarantine Station for Quality Control and Safety of Fishery Products in Medan I (BKIPM Medan I). Qualitative research method was conducted in BKIPM Medan I. Tilapia sample were taken from tilapia pond in Porsea and Laguboti, Toba Samosir, North Sumatera. Fifteen tilapias were taken from each pond. The sample criteria was 30 days old tilapia or tilapia that shown clinical symptom. RT-PCR method was perform at sample brain, kidney, and liver. The result from RT-PCR than analyzed and compared with the literature. The results of the study using the RT-PCR method on samples of tilapia (Oreochromis niloticus) from Porsea sub-district showed positive infected with TILV with the results of electrophoresis rna band TiLV appeared at 250 bp and the percentage of infestation of 66.67%. While fish from Laguboti subdistrict there is no indication of TILV disease with the percentage of tilapia infestation (Oreochromis niloticus) affected by Tilapia Lake Virus (TiLV) disease by 0%. While fish from Laguboti subdistrict there is no indication of TILV disease with the percentage of tilapia infestation (Oreochromis niloticus) affected by Tilapia Lake Virus (TiLV) disease by 0%. So it can be concluded that RT-PCR effectively detects TILV disease in tilapia fish.